A prospective study of spectrum of pulmonary tuberculosis in HIV sero positive patients - Kumari, Ganedi Seshu (International Journal of Advances in Medicine, 2021)
Background: Tuberculosis is the leading cause of death in India contributing to 30% of total global burden. Approximately 0.5 million people dies of TB annually and 5% of the incident TB cases in India have HIV. So it is important to understand the effect of tuberculosis and HIV on each other. HIV epidemics have leads to increased number of tuberculosis cases with various presentations. Methods: It is an observational cross-sectional study of patients with HIV positive and pulmonary TB. Patients were investigated for HIV positivity by HIV coomb's test, if positive confirmed by capillaries and tridot method. Some patients, who are diagnosed as having pulmonary Koch, are sent for HIV testing. CD4 cells count as tested in all patients with HIV positive and severity of pulmonary TB and relation with CD count is studied in all patients. Results: In chest x-ray of patients we have observed that upper zone infiltration was found in 10 (16.67%) patients, mid and lower zone infiltration was found in 19 (31.67%) patients, bilateral infiltration and miliary tuberculosis was found in 22 (36.67%). We have found that 9 (15%) patients were presented with fibro cavitary lesion. Conclusions: From present study we can conclude that tuberculosis and HIV is common between 3rd and 5th decade of life with male predominance. It was more common in daily labourer and BMI was 18.22±3.21 kg/m2. Fever, weight loss and cough was most common presentation and present in more than 90% patients pallor and lymphadenopathy was common finding and present in more than 50% patients.